PENCEGAHAN PERKAWINAN USIA ANAK DI INDONESIA PERSPEKTIF FILSAFAT HUKUM ISLAM: PENCEGAHAN PERKAWINAN USIA ANAK DI INDONESIA PERSPEKTIF FILSAFAT HUKUM ISLAM - Muhammad Farhan Alwani (Sekolah Tinggi Agama Islam Al-Hikmah 2, 2023)
This article discusses the importance of observing regulations to prevent marriage at a young age based on the philosophy of Islamic rules (Maqasid asy-Syari'ah). the author put the view that the above regulation is something that must be done. This shows that the application of child marriage to citizens is still relatively high. Mother and child deaths, low human resources, domestic violence & child abuse, and poverty are the effects that occur if child marriages are allowed to continue. Regulations for preventing child marriage are in line with maqasid asy-shari'ah, namely hifz an-nasl (protection of the soul-concern for the family), hifz an-nafs/hifz al-'ird (protection of the soul/honor/maintenance of human dignity), hifz al-'aql (multiplying mindsets & scientific research, prioritizing travel to seek knowledge, avoiding efforts to undermine brain performance), & hifz al-mal (protection of property, increasing the economy).